1983
DOI: 10.1017/s0033291700051060
|View full text |Cite
|
Sign up to set email alerts
|

Mental hospital and general hospital psychiatric units: a comparison of services within the same geographic area

Abstract: SYNOPSISA comparison was made between the characteristics of patients admitted to the only psychiatric hospital in Newfoundland, Canada, and those admitted to general hospital psychiatric units within the same area. Patients were compared on demographic characteristics, diagnosis, incidence of violence and suicidal attempts, treatment, length of stay and previous admissions. The results suggest that patients admitted to the mental hospital are more likely to be single, male, of lower socio-economic status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…Other studies from India have made similar observations. [1516] The researchers have observed that these females are more likely to be illiterate, married, and from a lower income group[1617] and the findings of our study corroborates the earlier reports.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies from India have made similar observations. [1516] The researchers have observed that these females are more likely to be illiterate, married, and from a lower income group[1617] and the findings of our study corroborates the earlier reports.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have made similar observations. 13,14 The majority of patients in our study belonged to the middle socio-economic status, with low level of literacy, and was with a rural background. It has been noted that patients belonging to families from the urban, literate, and higher socio-economic status, preferred to take treatment from private practitioners or from distant centers.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies conducted by Wroster and Malla et al also found similar observations. 18,19 This could be due to that these females are more likely to be illiterate, married, and from a lower income group. Similar findings and discussion was also quoted by Khanna and Lahariya et al 20,21 The majority of patients in our study belonged to the lower socio-economic status, with low level of literacy.…”
Section: Discussionmentioning
confidence: 99%